PERANAN STRATEGI PEMBELAJARAN KONFLIK KOGNITIF TERHADAP PEMAHAMAN KONSEP FISIKA PESERTA DIDIK MADRASAH ALIYAH NEGERI PANGKEP - Suryadi, Ahmad; Ali, Muhammad Sidin; Rusli, Muhammad Aqil (Jurnal Sains dan Pendidikan Fisika, 2015)
. This research employed True-Experimental research. It aimed to: (1) know the level of students’ physics conceptual understanding who were taught by implementing cognitive conflict instructional strategy (2) know the level of students’ physics conceptual understanding who were taught by implementing conventional instructional strategy (3) know the significant difference of students who were taught by implementing cognitive conflict instructional strategy and conventional instructional strategy in relation to their physics conceptual understanding. The variables of this research were cognitive conflict instructional strategy in which conventional instructional strategy as the independent variable and physics conceptual understanding of the students as the dependent variable. The research design was Post Test Only Control Group Design. The population of this research was class XI IPA Madrasah Aliyah Negeri Pangkep, from which class XI IPA 4 was chosen as experimental class and XI IPA 1 as control class. The number of the sample was 27 students of experimental class and 23 students of control class. At the end of the lesson, the students were provided a test in the form of physics conceptual understanding test to measure the students’ understanding of physics conceptual itself on the aspects of translation, interpretation, and extrapolation. The data analysis of this research employed descriptive statistic and inferential statistics analysis. Descriptive analysis results showed that the score of students’ physics conceptual understanding of experimental class taught using cognitive conflict instructional strategy in high category. The score of students from control class with conventional instructional strategy high category. The result of inferential analysis showed that there was a significant difference between the students’ physics conceptual understanding of who were taught with cognitive conflict instructional strategy and conventional instructional strategy.Penelitian ini adalah True Eksperiment yang bertujuan untuk: (1) mengetahui besarnya pemahaman konsep fisika peserta didik yang diajar dengan strategi pembelajaran konflik kognitif (2)  mengetahui besarnya pemahaman konsep fisika peserta didik yang diajar dengan strategi pembelajaran konvensional (3) mengetahui perbedaan yang signifikan antara  pemahaman konsep fisika peserta didik yang diajar dengan strategi pembelajaran konflik kognitif dan strategi pembelajaran konvensional. Variabel yang diteliti adalah strategi pembelajaran konflik kognitif dan strategi pembelajaran konvensional sebagai variabel bebas dan pemahaman konsep pembelajaran fisika sebagai variabel tak bebas. Desain penelitian adalah post test only control group design. Populasi penelitian adalah peserta didik kelas XI IPA Madrasah Aliyah Negeri Pangkep, dengan sampel XI IPA 4 berjumlah 27 sebagai kelas eksperimen dan XI IPA 1 berjumlah 23 sebagai kelas control. Pada akhir pembelajaran peserta didik diberi tes berupa tes pemahaman konsep fisika untuk mengukur pemahaman konsep fisika peserta didik dari aspek translasi, interpretasi, dan ekstrapolasi. Analisis data hasil penelitian ini menggunakan statistik deskriptif dan statistik inferensial. Hasil analisis deskriptif menunjukkan bahwa skor pemahaman konsep fisika peserta didik kelas eksperimen yang diajar dengan menggunakan strategi pembelajaran konflik kognitif berada pada kategori tinggi. Sedangkan, pada kelas kontrol dengan strategi pembelajaran konvensional juga berada pada kategori tinggi. Hasil analisis inferensial menunjukkan bahwa terdapat perbedaan yang signifikan antara pemahaman konsep fisika peserta didik yang diajar dengan strategi pembelajaran konflik kognitif dengan strategi pembelajaran konvensional.Kata Kunci:konflik kognitif, pemahaman konsep, pembelajaran konvensional